The Role of Country-of-origin Characteristics for Foreign Direct Investment and Technical Cooperation in Post-reform India - Axel Dreher; Peter Nunnenkamp; Krishna Chaitanya Vadlamannati (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2011)
The decisions of foreign investors on technical cooperation versus equity engagements and on the degree of ownership in FDI projects are likely to depend on their relative bargaining position vis-à-vis the host country. India provides an interesting case for analyzing the interplay between country-of origin-characteristics and host-country-characteristics and their respective effects on ownership decisions since opening up its economy to FDI in the early 1990s. We perform negative binominal regressions by making use of a unique dataset on about 24,500 technical cooperation and FDI projects by investors from 45 countries of origin over the 1991-2004 period. We find that relative market size, relative financial market development, relative risk, relative endowment of human capital and previous international experience significantly affect the type of engagement by foreign investors in post-reform India.
Keywords: F23; L24; 330; foreign investors; countries of origin; joint ventures; technical cooperation; India